Internet of Things: a Survey of the Advancements - V, Dhivya; Kumar Singh, Apoorva (International Journal of Engineering and Technology, 2018)
Internet of Things is a very broad concept and it is the name given to the interconnection of everyday devices to simplify, ease or provide useful information to the user. The International Telecommunication Union (ITU) defines IoT as "A global infrastructure for the information society, enabling advanced services by interconnecting (physical and virtual) things based on, existing and evolving, interoperable information and communication technologies". The name "Internet of Things" was first coined in 1999 by Kevin Ashton in a presentation to Proctor and Gamble. In this paper, we review the protocols, architecture, and applications surfacing in the region of the Internet of Things in the current years. The web of things has the capability of changing a great part of the world we live in. IoT comprises of an advanced cluster of sensors inserted into various "things" that ceaselessly transmits and shares significant information to different gadgets and cloud. Information that causes us better see how these things function and cooperate. But how all of this can happen on such a large scale with so many devices transmitting data? A simple answer to that would be the Internet of Things platform that brings diverse information and provides a common language for the devices and apps to communicate with each other.Â Â